Fragile X chromosome: clinical and cytogenetic studies on cases from seven families. Issue 3 (June 1983) - McDermott, A; Walters, R; Howell, R T; Gardner, A
Abstract : Results of detailed clinical and cytogenetic studies on 13 mentally retarded males and two heterozygous females (one normal and one retarded) are reported. Reference is made to technical modifications to enhance the incidence of expression of the fragile X. The addition of excess methionine to the fibroblast cultures (final concentration of 115 mg/l medium TC 199) was found to be particularly valuable, increasing the incidence of expression up to four-fold, and enabling the demonstration of the fragile X in fibroblasts when it could not be demonstrated in blood cultures in at least one case. Studies on replication patterns of the X chromosomes in the two heterozygous females showed that the fragile X chromosome was genetically active in a significantly greater proportion of cells (74%) in the mentally retarded female, whereas the normal X was active in a similar proportion (72%) in the carrier with normal intelligence.